Supervisi Pendidiksan Pada Masa Pandemi Covid-19 Di Madrasah Tsanawiyah Darul Ulum - Musonip Saputro; M Fathoni; Minnah El Widdah; Suryawahyuni Latief (Jurnal Pendidikan Islam, 2022)
The head of the madrasa must be able to carry out supervision activities to improve teacher performance. Supervision will help identify deficiencies in the teacher's learning process so far. Then look for joint solutions to improve learning activities in the classroom. This study reveals the performance of Darul Ulum Private MTS Madrasah teachers during the Covid-19 pandemic. The results of this study are: 1) Supervision is carried out in several stages, namely: planning, implementing and tracking. Supervision is carried out by the head of the madrasa and assisted by the teacher council. Matters that are subject to supervision include: administrative and academic supervision. Administrative supervision is carried out before the implementation of distance learning. Academic supervision is carried out by means of tutors taking virtual classes or online classes; 2) Obstacles in the implementation of supervision, namely the schedule of solid activities, computer literacy is still low, madrasa facilities supporting online learning are not enough, 3) Follow-up for some teachers who are not proficient in teaching methods is through the Zenius application to make it easier for teachers to take part in online training. In addition, madrasas also provide the facilities needed for these teachers to carry out distance learning in the form of providing adequate computers and equipment